The End of Alchemy by Mervyn King: A Review Essay - Farmer, Roger E. A. (Journal of Economic Literature, 2018)
I review The End of Alchemy by Mervyn King, published by W. W. Norton and Company in 2016. I discuss King’s proposed regulatory reform, the “pawnbroker for all seasons” (PFAS), and I compare it to an alternative solution developed in my own work. I argue that unregulated trade in the financial markets will not, in general, lead to Pareto-optimal allocations. As a consequence, solutions like the PFAS that correct problems with existing institutions are likely to be circumvented by the development of new ones. (JEL D81, D82, E44, G01, G18, G28, L51)